The Effectiveness of Monetary Policy: Evidence from China - Chi, Qishui (Archives of Business Research, 2016)
The purpose of this paper is to provide China’s empirical evidence on the real effectsof monetary policy from 1998:12 to 2012:08 by means of structural change analysis.The study shows that the structural changes of money supply at 2003:05, the end of 2008 and early of 2009 impact real output and prices efficiently, but the situations are opposite at 2000:12, 2001:06 and 2003:12. After investigating the interestrate transmission channel of monetary policy, this article draw a conclusion that the conflicting interest rate policy contrary to the overall objective of China’s central bank often makes easy or tight monetary policy work inefficiently.Therefore, it matters profoundly to ensure that the interest rate policy matches the main objectives of monetary policy